Impacts of spiritual and cultural intelligence on leadership effectiveness: a conceptual analysis - Osman Gani, Aahad M.; Hassan, Zubair (World Academy of Islamic Management (WAIM), 2018)
The purpose of this paper is to examine the impacts of Spiritual and Cultural Intelligence on Leadership effectiveness in global environment using the available current literature. Through the review of past work, the most dominant concept of cultural intelligence was introduced by Ang et al. (2007) where four dimensions of cultural intelligence were proposed (metacognitive intelligence, cognitive intelligence, motivational intelligence, and behavioural intelligence). In terms of spiritual intelligence, Zohar and Marshall (2005) and Reeve (2005) work could be a very useful and gain much attention in the field. Both framework to measure cultural intelligence and spiritual intelligence were empirically examined in relations with leadership effectiveness. A mixed result was reported. However it is important to note that majority of the study indicated that Cultural intelligence and Spiritual Intelligence have positive and significant impact on global leadership effectiveness in terms of decision making, performance, and commitment. Therefore this paper is proposed to collect data using three instruments: Ang et al. (2007)’s four cultural intelligence dimensions and the measurement tool will be used to measure cultural intelligence. To measure Spiritual Intelligence, Zohar and Marshall (2005)’s measurement tools will be used and to measure leadership effectiveness, Kouzes and Posner (1995). This study will be useful for individual managers and organisation in developing global mind-set and effectiveness of their managers in global environment and working with diverse workgroups.